2019
DOI: 10.3168/jds.2018-15349
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of lameness and associated risk factors on dairy farms in the Maritime Provinces of Canada

Abstract: Lameness in dairy cattle is a major issue for the industry due to the effects on the welfare of the animal, the economic impact, and consumer perception. The aim of this study was to determine the prevalence of lameness and explore potential risk factors in the Maritime Provinces of Canada. Cows were scored for lameness and potential risk factors and were assessed in 46 freestall herds and 33 tiestall herds in Nova Scotia, New Brunswick, and Prince Edward Island. In freestall herds, lameness was assessed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
3
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 44 publications
(85 reference statements)
5
28
3
2
Order By: Relevance
“…The 65 freestall herds included in study 1 had a lameness prevalence of 20% (95% CI: 18.4-24.3), consistent with reported estimates of 21% in the Maritime provinces of Canada (Jewell et al, 2019) and 19% last reported in Alberta (Solano et al, 2015). The latter comparison could be reflective of the continuing lack of prevention and control strategy uptake by producers in the province.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The 65 freestall herds included in study 1 had a lameness prevalence of 20% (95% CI: 18.4-24.3), consistent with reported estimates of 21% in the Maritime provinces of Canada (Jewell et al, 2019) and 19% last reported in Alberta (Solano et al, 2015). The latter comparison could be reflective of the continuing lack of prevention and control strategy uptake by producers in the province.…”
Section: Discussionsupporting
confidence: 77%
“…For instance, North American studies have reported estimates that range from 10 to 55% (von Keyserlingk et al, 2012;Cook et al, 2016;Westin et al, 2016;Adams et al, 2017). Recent studies in Canada, including herds from Alberta, Ontario, Quebec, and the Maritimes, have reported prevalence estimates with a smaller range of 19 to 24% (Solano et al, 2015;Jewell et al, 2019). Although lameness detection remains a subjective measure partly because of a variety of locomotion scoring systems, the Canadian Dairy Code of Practice considers a lameness prevalence of 10% to be an acceptable upper limit (National Farm Animal Care Council, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Poor leg hygiene increases the development of infectious lesions or claw horns by exposing the feet to manure and moisture, which affects the health of the claws. Cows housed on wet litter were 2.5 times more likely to be lame than those housed on dry litter (Jewell et al, 2019). According to experiments conducted by Gregory (2004) and Gregory et al (2006), exposure of cow's hooves to urine and fecal contamination causes the hoof to swell and soften.…”
Section: O N L I N E F I R S T a R T I C L Ementioning
confidence: 99%
“…Time out of the freestall pen milking can also negatively affect the time available for rest (Gomez and Cook, 2010). It is recommended that the facility be designed so that time spent milking each day should not exceed 3 h total (Cook, 2019) to optimize the time available for rest and reduce the risk for lameness (Jewell et al, 2019). Indeed, Charlton et al (2014) showed that no farm achieved more than 12 h of lying time/d when stocking rates exceeded 100% or when time milking exceeded 3.7 h/d.…”
Section: Housing and Management Factors Influencing Resting Behaviormentioning
confidence: 99%